Relationship of Early Vitamin D Concentrations and Gestational Diabetes Mellitus in Indian Pregnant Women - Dwarkanath, Pratibha; Vinotha, Ponnusamy; Thomas, Tinku; Joseph, Siji; Thomas, Annamma; Shirley, George; Sheela, C. N.; Mehta, Saurabh; Kurpad, Anura V. (Frontiers in Nutrition, 2019)
Background: A high prevalence of vitamin D deficiency exists in pregnant Indian women (~90%). Increasing evidence suggests a pivotal role for vitamin D in maintaining normal glucose homeostasis. We aimed to determine the association between maternal vitamin D concentrations in early pregnancy and the risk of gestational diabetes mellitus (GDM). Methods: A prospective observational study was conducted on healthy pregnant women (n=392) attending routine antenatal care at St. John’s Medical College Hospital, Bangalore recruited at ~12 weeks of gestation. At baseline, details on socio-economic status, obstetric history, dietary intakes and anthropometry were collected. Venous plasma total vitamin D concentration was assessed using tandem liquid chromatography mass spectrophotometry (LC-MS/MS). Oral glucose tolerance test (OGTT) at recruitment, followed by glucose tolerance test (GTT) at mid-pregnancy was conducted. GDM was diagnosed and confirmed using the International Association of Diabetes and Pregnancy Study Groups (IADPSG) classification. Univariate and adjusted logistic regression models were used to evaluate the associations between total vitamin D concentrations at enrollment with GDM. Results: Of the cohort, 10.2% were diagnosed as GDM. Women with GDM were older (26 vs. 24 years) and heavier (51.6 vs. 51.2 kg) compared to the rest. A higher prevalence of GDM was observed among women with 1st trimester plasma total vitamin D in the lowest quartile (≤23.6 nmol/L) compared to the subjects in the other three quartiles (16.1 vs. 8.6%, p=0.033). Adjusted multivariable regression analysis showed that women in the lowest quartile of plasma total vitamin D had twice the odds of GDM compared to women belonging to the remaining quartiles [OR=2.32 (95%CI: 1.10, 4.91), p=0.028]. Conclusions: Low plasma total vitamin D concentrations in early pregnancy may be associated with a higher risk of GDM.